2019
DOI: 10.1002/cpt.1403
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pharmacogenetic Variants in HIV/Tuberculosis Coinfected Patients in Uganda in the SOUTH Study

Abstract: Unsatisfactory treatment outcomes have been reported in patients coinfected with HIV/tuberculosis (TB). The aim of this study was to assess the influence of single‐nucleotide polymorphisms (SNPs) in genes encoding for proteins involved in antitubercular drug disposition or effect. A pharmacogenetic study was conducted in Kampala, Uganda, where all analysis was performed. The impact of SNPs on antitubercular drug exposure, adverse events, and treatment outcomes was evaluated in patients coinfected with HIV/TB r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The proposed dosing strategy is restricted by resources to determine acetylator status. However, genotype‐based tailoring of antitubercular therapy could be used in hard‐to‐treat patients even if resources are limited …”
Section: Discussionmentioning
confidence: 99%
“…The proposed dosing strategy is restricted by resources to determine acetylator status. However, genotype‐based tailoring of antitubercular therapy could be used in hard‐to‐treat patients even if resources are limited …”
Section: Discussionmentioning
confidence: 99%
“…The association of SLCO1B1 rs4149056, rs2306283, rs4149032 and rs11045819 polymorphisms with rifampicin PK reported in certain studies were not replicated in other studies. Recent studies from the African population have not found any association with SLCO1B1 polymorphisms and rifampicin exposures among TB patients 22,26,27 . Similarly, studies conducted by Ramesh et al 28 and Jeremiah et al 29 in the Indian and Tanzanian population, respectively, did not report any association of SLCO1B1 polymorphisms with plasma rifampicin exposures.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies from the African population have not found any association with SLCO1B1 polymorphisms and rifampicin exposures among TB patients. 22,26,27 Similarly, studies conducted by Ramesh et al 28 and Jeremiah et al 29…”
Section: Allegra Et Al Reported Higher Plasma Rifampicin Concentrations In Tbmentioning
confidence: 92%
“…However, recent studies from the African population have not found any association with SLCO1B1 polymorphisms and RF exposures among TB patients [48,51,52]. Similarly, studies conducted by Ramesh et al and Jeremiah et al in the Indian and Tanzanian population, respectively, did not report any association of SLCO1B1 polymorphisms with plasma RF exposures (Table 1) [53,54].…”
Section: Slco1b1mentioning
confidence: 90%
“…Reports from the Brazilian population revealed the frequencies of FokI TT, TC and CC genotypes to be 44.6%, 41.4% and 14%, respectively [80]. Calcagno et al reported that the VDR regulatory region Cdx2 variant was not associated with any significant changes in the plasma RF concentration [52].…”
Section: Vitamin D Pathway Gene Polymorphismsmentioning
confidence: 99%